2020
DOI: 10.1002/ehf2.12533
|View full text |Cite
|
Sign up to set email alerts
|

Role of PCSK9 in the course of ejection fraction change after ST‐segment elevation myocardial infarction: a pilot study

Abstract: Aims Proprotein convertase subtilisin/kexin type 9 (PCSK9) has emerged as a therapeutic target for reducing plasma low‐density lipoprotein cholesterol. Beyond lipid control, recent findings suggest a deleterious effect of this protein in the pathogenesis of postmyocardial infarction left ventricle remodelling and heart failure‐related complications. The aim of this study was to assess the relationship between circulating PCSK9 and 6 month cardiac magnetic resonance imaging‐derived left ventricular ejection fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
2
14
0
4
Order By: Relevance
“…Recently it was reported that PCSK9 plasma levels are associated with a reduced ejection fraction in patients suffering from ST-segment elevation myocardial infarction [24]. Furthermore a distinct function of cardiomyocyte-derived PCSK9 has only been reported for neonatal mouse cardiomyocytes, where under hypoxic conditions the release of PCSK9 determines autophagy in these cells [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was reported that PCSK9 plasma levels are associated with a reduced ejection fraction in patients suffering from ST-segment elevation myocardial infarction [24]. Furthermore a distinct function of cardiomyocyte-derived PCSK9 has only been reported for neonatal mouse cardiomyocytes, where under hypoxic conditions the release of PCSK9 determines autophagy in these cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCSK9 inhibitors have been shown to improve cardiac function in rats with acute I/R injury when applied prior to ischemia [ 26 ]. Finally a clinical study reports a correlation between high PCSK9 plasma levels and a reduction of left ventricular ejection fraction in patients that suffered from ST-segment elevation myocardial infarction [ 24 ]. These studies demonstrate, similar to our findings, a positive effect of PCSK9 inhibition or genetic deletion on cardiac function after ischemia or I/R injury in vivo [ 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PCSK9 inhibitors antagonize the interaction between PCSK9 protein and CD36 receptor on platelet surface, thereby affecting CMVO, the risk of NR, and the following IS extension [223]. Consistently, lower circulating levels of PCSK9 were found to be inversely associated with LVEF at six months since the STEMI event [224].…”
Section: Pcsk9 Inhibitorsmentioning
confidence: 77%
“…This suggests that extracellular PCSK9 mediates the effect. Furthermore, ischemia/reperfusion triggers the cardiac and hepatic release of PCSK9 as well as its cardiac expression ( Chandrakala et al, 2012 ; Zhang et al, 2014 ; Minana et al, 2020 ). HIF links ischemia to the upregulation of PCSK9 ( Ding et al, 2018b ).…”
Section: The Role Of Pcsk9 In Striated Musclesmentioning
confidence: 99%